Long Term Cultivation Effects on Soil Properties in Pastures - Durak, A.; Gunal, H.; Akbas, F.; Kilic, S. (Asian Journal of Chemistry, 2010)
Four soil profiles were examined to determine and compare the effect of soil management practices on various soil physical, chemical and morphological features. Soils were developed in an alluvium over lacustrine materials. The locations of pits studied were selected based on the distance from river and profIles were excavated two from native pasture (never been cultivated) and the other two from cultivated field (15 years of cultivation). Soil moisture contents of cultivated lands were higher than that of pasture field. Organic matter content of surface horizons were decreased almost 50% in cultivated fields due to the increasing decomposition rate of organic matter in tilled fields. Soluble salt content was increased at about 90 cm depth in cultivated land while in pastures high soluble salt contents were observed closer to the surface (about 50 cm depth). Calcium carbonate nodules and masses were described at around 60 cm of the soil surface in cultivated field. Results indicated that long-term management practices resulted in changes in soils, both in physical and chemical properties.